Age–Related Difference of Substances Controlling Mitoses in Lymph: A New Way of Drugs Design and Development - A. Kuznetsov; Y. Almabayev; I. Fackhradiev; A. Almabaeva; J. Serikpayev; B. Tanabayev (Current Aspects in Pharmaceutical Research and Development Vol. 8, 2022)
Introduction: Mitosis is a basic age–related process. Mitoses are found in various tissues and are controlled by mediators. Cytokines and hormones, for example, are used as drugs to treat cancer, graft–versus–host disease, and other diseases. Objective: Our goal is to evaluate existing research on age–related mitoses, cytokines, and hormones in lymph (body fluid), specifically in thoracic duct lymph (TDL) in norm, and to use it in new drug design and development. Methods: We investigated the data banks of PubMed/Medline, World Cat, Google and Index Copernicus searching for articles published in the past four decades. Results: Three articles characterised some morphological properties and quantitative changes in age-related mitoses in normal TDL. One study looked at the quantitative and morphological characteristics of TDL lymphocytes in healthy and thyroxin-treated people. Several studies on the physiology of angiotensins, insulin, and steroid hormones were conducted. Many recent publications have focused on proliferation and mitosis mediators. Interleukins are being studied in lymph for their antigen–stimulation and other effects. The effect of age on the immune system, particularly mitoses, was discovered. Despite advances in the field of drug design, there is a perception of failed attempts to solve some problems using reductionist methods. To develop a drug, several complex multistep schemes must be completed, cytotoxicities must be controlled, and the results must be compared. Conclusion: The data presented above show that the immune system changes with age, both in norm and in impact. The differences and changes in TDL mitosis mediators in mature and immature organisms have not been studied. New drug components must be developed. It is proposed that the differences in TDL mitosis mediators between healthy newborns (neonatal, immature) and adults (mature) can be used to develop new drugs for cancer, graft–versus–host disease, and other diseases.